TERRORIST THREAT ON THE HIGH SEAS ANALYSIS OF SOME ASPECTS OF THE RIGHT OF VISIT AND SELF-DEFENCE - Corthay, Eric (Indonesian Journal of International Law, 2017)
Vessels of all sizes can be used in a number of ways by terrorists, they can utilize a vessel as a means, a weapon, a bomb, or as a disruption tool. When a terrorist attack happens, it is already too late, hence the critical importance for the international community to take timely, accurate and efficientex ante factosteps.Counter-terrorism measures implemented on the high seas to prevent maritime terrorist attacks from occurring are possible but limited by the international law and notably the law of the sea. To some extent, the law of the sea limits counter-terrorism efforts. On the high seas, enforcement measures against terrorists or terrorist-related activities on board foreign vessels are restricted by the principle of exclusivity of flag State jurisdiction (a). Nevertheless, the application of the principle can be derogated from by the right of visit which provides for, under certain conditions, some leeway to States in their fight against maritime terrorism (b). it is difficult to justify interdiction operations carried out in order to counter terrorist threats on the high seas by the right of self-defence. The first reason relates to the differences in rationale and legal regime between the force deployed during interdiction operations and the one used in self-defence (a); the second reason concerns the existence or not of a right of anticipatory self-defence (b).